Grass carp SARM1 and its two splice variants negatively regulate IFN-I response and promote cell death upon GCRV infection at different subcellular locations. Issue 1 (January 2015) - Yan, Nana; Su, Jianguo; Yang, Chunrong; Rao, Youliang; Feng, Xiaoli; Wan, Quanyuan; Lei, Chuzhao
Highlights Two novel splice variants CiSARM1s1 and CiSARM1s2 only retain ARM domain(s). CiSARM1 and CiSARM1s1 are located in mitochondria, while CiSARM1s2 resides in the whole cell. CiSARM1 inhibits GCRV-triggered IFN-I response by affecting the molecules in TRIF-, MyD88- and IPS-1-dependent pathways. CiSARM1s1 and CiSARM1s2 inhibit GCRV-triggered IFN-I response by suppressing mediators in MyD88 and IPS-1signal pathways. CiSARM1, CiSARM1s1 and CiSARM1s2 promote GCRV-induced cell death.